2019
DOI: 10.3389/fpsyt.2018.00726
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Express Mu Opioid Receptor: Insights From Transcriptomics and Fluorescent Reporter Mice

Abstract: Background: Microglia activation contributes to chronic pain and to the adverse effects of opiate use such as analgesic tolerance and opioid-induced hyperalgesia. Both mu opioid receptor (MOR) encoded by Oprm1/OPRM1 gene and toll like receptor 4 (TLR4) have been reported to mediate these morphine effects and a current question is whether microglia express the Oprm1 transcript and MOR protein. The aim of this study was to characterize Oprm1-MOR expression in naive murine and human microglia, combining transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 101 publications
(146 reference statements)
5
33
0
Order By: Relevance
“…Using immunofluorescence in transgenic mice expressing MOP receptors in microglia (CX3CR1-eGFP-MOP-mCherry), the percentage of MOP receptor-positive microglial cells ranged between 35 and 52% in brain, and between 37 and 42% in the spinal cord. The presence of MOP receptor protein in Golgi apparatus suggested that the receptors might be synthetized by microglia (100). Utilizing MOP-mCherry mice and double labeling in wild-type mice using astrocyte marker and MOP receptor antibodies (whose staining specificity was confirmed in MOP receptor knockout mice), MOP receptor protein was detected in astrocytes in various brain regions (107).…”
Section: Gliamentioning
confidence: 99%
“…Using immunofluorescence in transgenic mice expressing MOP receptors in microglia (CX3CR1-eGFP-MOP-mCherry), the percentage of MOP receptor-positive microglial cells ranged between 35 and 52% in brain, and between 37 and 42% in the spinal cord. The presence of MOP receptor protein in Golgi apparatus suggested that the receptors might be synthetized by microglia (100). Utilizing MOP-mCherry mice and double labeling in wild-type mice using astrocyte marker and MOP receptor antibodies (whose staining specificity was confirmed in MOP receptor knockout mice), MOP receptor protein was detected in astrocytes in various brain regions (107).…”
Section: Gliamentioning
confidence: 99%
“…As mentioned in the section above, several drugs of abuse, but particularly opioids, have been shown to directly activate microglia through TLR4 and/or mu (μ) opioid receptors on resident microglia [ 199 , 325 ], whereby μ opioid receptor activation accentuates lipopolysaccharide (LPS)-induced microglia activation-mediated NF-kB signaling [ 103 , 141 ]. Importantly, LPS is both a microbial product and can be exogenously infused to induce sepsis, and subsequently, an immune response.…”
Section: Developing An Understanding Of the Interactions Between Neurmentioning
confidence: 99%
“…Drugs reported to selectively attenuate glial inflammation block morphine conditioned place preference and attenuate symptoms of opioid withdrawal (Narita et al 2006 ; Hutchinson et al 2009 ; Liu et al 2010 ). μ (MOR), δ (DOR), and κ (KOR) opioid receptors are expressed by subsets of astrocytes and microglia (Stiene-Martin and Hauser 1991 ; Eriksson et al 1992 ; Stiene-Martin et al 1993 ; Ruzicka et al 1995 ; Gurwell et al 1993 ; Hauser et al 1996 ; Turchan-Cholewo et al 2008 ; Maduna et al 2018 ) and are involved in opioid tolerance and dependence to varying degrees (Kieffer and Gaveriaux-Ruff 2002 ; Berger and Whistler 2010 ; Morgan and Christie 2011 ). Despite some reports of morphine triggering immune activation via Toll-like receptor 4 (TLR4) (Terashvili et al 2008 ; Hutchinson et al 2010 ; Coller and Hutchinson 2012 ; Hutchinson et al 2012 ; Theberge et al 2013 ; Lacagnina et al 2017 ) by binding to a myeloid differentiation protein-2 intermediary (Wang et al 2012 ), this is contrary to the typical actions of opiates, which by themselves (and in the absence of a priming event such as HIV co-exposure) tend to suppress immune function (Eisenstein 2019 ).…”
Section: Overviewmentioning
confidence: 99%